Identification of candidate olfactory genes in Leptinotarsa decemlineata by antennal transcriptome analysis - Liu, Yang; Sun, Lujuan; Cao, Depan; Walker, William B.; Zhang, Yongqiang; Wang, Guirong (Frontiers in Ecology and Evolution, 2015)
The sense of smell is critical for the survival of insects, by which insects detect the odor signals in the environment and make appropriate behavioral responses such as host preference, mate choice, and oviposition site selection. The antenna is the main olfactory organ in insects. Multiple antennal proteins have been suggested to be involved in olfactory signal transduction pathway such as odorant receptors (ORs), ionotropic receptors (IRs), odorant binding proteins (OBPs), chemosensory proteins (CSPs) and sensory neuron membrane proteins (SNMPs). In this study, we identified several olfactory gene subfamilies in the economically important Coleopteran agricultural pest, Leptinotarsa decemlineata, by assembling the adult male and female antennal transcriptomes. In the male and female antennal transcriptome, we identified a total of 37 OR genes, 10 IR genes, 26 OBP genes, 15 CSP genes and 3 SNMP genes. Further all candidate ORs were validated to be expressed in male or female antenna by semi-quantitative reverse transcription PCR. Most of the candidate OR genes have similar expression level in male and female. A few OR genes have been detected as male-specific (LdecOR6) or male-bias (LdecOR5, LdecOR12, LdecOR26 and LdecOR32) expression. As well as that, two OR genes (LdecOR3 and LdecOR29) were proved to be expressed higher in female. Our findings make it possible for future research of the olfactory system of L. decemlineata at the molecular level.